The Wecken problem for coincidences of boundary preserving surface maps - Kelly, Michael R. (Topological Methods in Nonlinear Analysis, 2023)
We prove a Brooks type coincidence minimization result for boundary preserving maps on compact surfaces with boundary. As an application we obtain non-boundary Wecken results for pairs of maps f,g(X,X) → (X,X) for most surfaces X.